As contribuições do Programa Institucional de Bolsas de Iniciação à Docência (PIBID) para a construção de saberes sobre a docência : o caso do PIBID-Biologia da Universidade Federal de São Carlos - Santos, Mariana dos (Universidade Federal de São Carlos, 2016)
This work falls within the scope of the investigation of the initial teacher training, investigating the Institutional Scholarship Program Introduction to Teaching. This is a case study in which it is carried out an analysis of PIBID-Biology subproject of the Federal University of São Carlos (UFSCar), which is part of PIBID UFSCar-institutional project. From an analysis of all documents relating to the implementation of the project at all levels (national, institutional and subproject) as well as the interview with researchers involved in the construction of these projects, we built a description of the processes involving the construction of the national project, as well as the institutional design and, finally, the subproject Biology UFSCar. This first step was the context for understanding, through analysis of reflective portfolios produced by scholars, the dimensions of teaching knowledge built by undergraduates as scholarship students from PIBID. In light of the training teacher references (NÓVOA, 2009; ANDRÉ, 2012, GATTI, BARRETTO & ANDRÉ 2011, Zeichner, 2010, among others), knowledge of the teachers (PEPPER, 2005 Tardif, 2000, 2007) and also Complexity Theory (BONIL & PUJOL, 2008; RIBERAYGUA, 2012; MORIN, 2004, 2005), we realized that, despite the PIBID have characteristics that approach a complex and dynamic model, students have many difficulties in view their performance as part of a complex system that involves not only the classroom but the entire surroundings. We understand that this may occur because not always the PIBID works in coordination with the context , undermining thus functioning as a dynamic and complex system , requiring several adjustments and improvements in this program.
Keywords: Formação inicial de professores de Ciências e Biologia; Programa Institucional de Bolsas de Iniciação à Docência; Saberes docentes; Teoria da Complexidade; Initial training of science and biology teachers; Institutional Program Initiation Scholarships to Teaching; Teachers knowledge; Complexity Theory; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO